Formation of an aminovinyl-cysteine residue in thioviridamides occurs through a path independent of known lanthionine synthetase activity. Issue 5 (20th May 2021) - Qiu, Yanping; Liu, Jingyu; Li, Yuqing; Xue, Yanqing; Liu, Wen
Summary: 2-Aminovinyl-cysteine (AviCys) is a thioether amino acid shared by a variety of ribosomally synthesized and posttranslationally modified peptides (RiPPs). Based on investigations into the biosynthesis of thioviridamide RiPPs in Streptomyces sp. NRRL S-87, we here report a path for the formation of this unusual thioether residue. This path relies on four dedicated proteins: phosphotransferase TvaCS-87, Lyase TvaDS-87, kinase homolog TvaES-87, and LanD-like flavoprotein TvaFS-87 . TvaES-87 plays a critical role in effective AviCys formation. During the posttranslational modifications of the precursor peptide, it works with TvaFS-87 to form a minimum AviCys synthetase complex, which follows the combined activity of TvaCDS-87 for Thr dehydration and catalyzes Cys oxidative decarboxylation and subsequent Michael addition of the resulting enethiol nucleophile onto the newly formed dehydroamino acid residue for cyclization. With TvaES-87, TvaFS-87 activity for Cys processing can be coordinated with TvaCDS-87 activity for minimizing competitive or unexpected spontaneous reactions and forming AviCys effectively. Graphical abstract: Highlights: Formation of an AviCys residue in thioviridamides relies on four dedicated proteins A lyase functionally associates with a phosphotransferase for Thr dehydration Kinase homolog TvaE plays a critical role in effective AviCys formation TvaE works with a LanD-like flavoprotein to form a minimum AviCys synthetase complex Abstract : Qiu et al. report 2-aminovinyl-cysteine formation in the biosynthesis of ribosomally synthesized thioviridamides. A kinase homolog works with a LanD-like flavoprotein to form a minimum 2-aminovinyl-cysteine synthetase complex. Following combined phosphotransferase-lyase activity for Thr dehydration, this complex catalyzes Cys oxidative decarboxylation and subsequent Michael addition to provide an unsaturated thioether linkage.